HUBUNGAN SIKLUS KEMOTERAPI DENGAN KEJADIAN CHEMOTHERAPY INDUCED NAUSEA AND VOMITING (CINV) - Mutia Dwi Sagita (Ensiklopedia of Journal, 2023)
The incidence of nausea and vomiting is one of the side effects of chemotherapy that has an impact on the continuity of breast cancer treatment. Objective: This Study aimed to know relationship between chemotherapy cycles with incidence of chemotherapy induced nausea and vomiting (CINV). Methods: This study used an exploratory descriptive design. The research sample was 22 breast cancer patients with consecutive sampling technique. Data analysis used the Kruskall Wallis test. Results : There was a relationship between Chemotherapy Induced Nausea And Vomiting (CINV) and chemotherapy cycles (p value=0.013). Conclusion : There is a decrease in Chemotherapy Induced Nausea And Vomiting (CINV) along with an increase in chemotherapy cycles. It is recommended that nurses can carry out monitoring in the management of patients undergoing chemotherapy treatment.